Rapid whole genome sequencing in newborn screening for metabolic diseases - Zheng, Jun; Yang, Xin (Frontiers in Pediatrics, 2025)
Background and purposeMetabolic disorders, which are estimated to include approximately 1,500 distinct conditions such as urea cycle disorders, lysosomal storage diseases, and mitochondrial dysfunctions, pose a significant clinical challenge due to their genetic heterogeneity and rapid onset of symptoms in newborns. Delays in diagnosis often lead to irreversible damage or mortality. Rapid whole genome sequencing (rWGS) has emerged as a transformative diagnostic tool, offering comprehensive genetic insights within 24–72 h.Materials and methodsThis study reviews the application of rWGS in the early detection and management of metabolic diseases, emphasizing its role in overcoming limitations of traditional diagnostic methods.ResultsThe integration of rWGS into clinical workflows offers a high diagnostic yield, exceeding 50% in neonatal intensive care units (NICUs), where timely interventions are critical. Utilizing advanced sequencing platforms, such as Illumina NovaSeq and Oxford Nanopore, coupled with optimized bioinformatics pipelines, rWGS enables precise variant identification and prioritization. Key findings highlight its capacity to accelerate diagnosis, inform therapeutic decisions, and reduce diagnostic odysseys. For instance, identifying pathogenic variants in genes allows early initiation of targeted therapies, significantly improving outcomes.ConclusionsDespite its transformative potential, challenges remain, including cost, data interpretation, and equitable access. Addressing these barriers through investments in infrastructure, training, and policy frameworks will be crucial for broader implementation. This review underscores the critical role of rWGS in neonatal care and highlights its promise as a cornerstone of precision medicine, paving the way for improved diagnostic accuracy and patient outcomes in metabolic diseases.